Analisis Struktur Vegetasi dan Potensi Serapan Karbon Tumbuhan di Kawasan Cagar Alam Tangale Kabupaten Gorontalo - Kirsten Caroline Donsi; Dewi Wahyuni K. Baderan; Abubakar Sidik katili; Marini Susanti Hamidun; Jusna Ahmad; Nurma Rosalia (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This study aims to determine the composition and structure of vegetation and estimate the potential for carbon dioxide absorption in the Tangale Nature Reserve Area, Gorontalo Regency. The method used in this study is the determination of sampling locations carried out by purposive sampling, making multilevel plots, analyzing vegetation structure, and estimating tree biomass is done non-destructively based on measuring the height and diameter of trees at breast height (DBH), while for lower plants it is done destructively and litter is taken all in the plot area to be weighed wet and dry weight and then estimating biomass, C reserves, and CO2 uptake. The results showed that the vegetation composition consisted of 18 species dominated by the Magnoliopsida class. The highest Important Value Index is found at each observation station. Calculation of biomass value, C reserves, and CO2 uptake at each observation station showed varying results because they were influenced by vegetation type, vegetation density, vegetation composition and structure, and environmental factors. The total value of CO2 uptake by vegetation in the Tangale Nature Reserve Area is 5,304.393 tons of CO2/ha. This research provides a better understanding of carbon sequestration potential in conservation areas to support environmental conservation and climate change mitigation efforts.